2008
DOI: 10.1093/hmg/ddn061
|View full text |Cite
|
Sign up to set email alerts
|

Defective body-weight regulation, motor control and abnormal social interactions in Mecp2 hypomorphic mice

Abstract: MeCP2 is an abundant protein that binds to methylated cytosine residues in DNA and regulates transcription. Mutations in MECP2 cause Rett syndrome, a severe neurological disorder that affects approximately 1:10 000 females. Mice lacking MeCP2 have been generated and constitute important models of Rett syndrome. However, it is yet unclear whether certain physiological events are sensitive to a decrease, rather than a complete lack of MeCP2. Here we report that a Mecp2 floxed allele (Mecp2(lox)) that was generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 48 publications
10
46
1
Order By: Relevance
“…24,29 This apparent inconsistency could be due to small differences in patterns of transgene expression, or to the different time point in which the mice were tested (7 weeks of age (this study) versus 12 weeks). Also, subtle phenotypic manifestations not analyzed in this study, such as social behavior, could still be present in Mecp2 À/y mice expressing transgenic MeCP2-e1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…24,29 This apparent inconsistency could be due to small differences in patterns of transgene expression, or to the different time point in which the mice were tested (7 weeks of age (this study) versus 12 weeks). Also, subtle phenotypic manifestations not analyzed in this study, such as social behavior, could still be present in Mecp2 À/y mice expressing transgenic MeCP2-e1.…”
Section: Discussionmentioning
confidence: 94%
“…24,25 Thus, we determined the level of expression of transgenic MeCP2 by comparing the immunoreactivity for MeCP2 in protein extracts obtained from a variety of brain regions of transgenic and wild-type mice. Analysis of the western blot results indicated that expression of MeCP2-e1 in e1-TgH and e1-TgL varied between brain regions, averaging at 40 and 15% of MeCP2 wild-type expression, respectively (data not shown).…”
Section: Expression Of Isoform-specific Cdnas In Transgenic Micementioning
confidence: 99%
“…We removed Mecp2 from cholinergic neurons by breeding mice carrying a Mecp2 allele flanked by loxp sites (Mecp2 flox/− ) [30] with Cre transgenic (Chat-IRESCre) mice (Supplementary information, Figure S1A). To determine Mecp2 deletion in cholinergic neurons, we stained BF sections with MeCP2 and ChAT, a marker for cholinergic neurons ( Figure 1A).…”
Section: Selective Deletion Of Mecp2 In Cholinergic Neurons Led To Pamentioning
confidence: 99%
“…In this regard, relatively subtle decreases in MeCP2 expression are sufficient to induce behavioral impairments in mice (Samaco et al, 2008;Kerr et al, 2008), and decreases in brain MeCP2 levels have been reported in neurological conditions such as Angelman syndrome, attention deficit hyperactivity disorder, and general autism (Nagarajan et al, 2006;Neul, 2012;Gonzales and LaSalle, 2010). Thus, the neural link we illustrate here between MeCP2 and GAT-1 expression may be worthy of assessment in other conditions in which imbalances of excitatory and inhibitory tone are believed to have a role in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%